PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN MEMECAHKAN MASALAH DAN HASIL BELAJAR KOGNITIF BIOLOGI SISWA KELAS VII SMP NEGERI 14 SURAKARTA TAHUN PELAJARAN 2011/2012 - Siswanto, Siswanto; Maridi, Maridi; Marjono, Marjono (Pendidikan Biologi, 2012)
ABSTRACT ? This  research  aims  to  determine the effect of  PBL  learning model  of problem-solving skills and cognitive learning outcomes biology class VII students of SMP Negeri  14  Surakarta. PBL  model  is a model  of learning  by  forcing students  to  practical  problems  or  as a  foothold  in  learning,  in other words, students learn  through  the problems. Given the  problems  the students  are challenged  to  find  / search for a solution of  real world problems can be resolved as a group  (in collaboration). The cooperation will enable students  in learning  to improve problem-solving skills and cognitive learning outcomes. This research is a  Quasi  Experimental  research  design  using a  pretest-postest Control Group. Population is all students in grade VII Junior High School 14 Surakarta with cluster random sampling technique using sampling. Aspects of data collection techniques and problem-solving skills using the cognitive learning outcomes tests are analyzed using statistical tests anacova. Keywords: Model  of  Problem Based  Learning  (PBL),  Problem  Solving  Ability, Cognitive Sciences Learning Outcomes